Umbilical fissure vein, anatomical variation and potential surgical application. Issue 7 (24th May 2021) - Idrees, Marwan; Zhang, Leon; Al‐Ogaili, Zeyad; Yau, Ho‐Cing V.; Zhu, Shaun; Jaques, Bryon; Foo, Jonathan; Mou, Lingjun
Abstract: Background: The umbilical fissure vein (UFV) is a hepatic vein that travels within the umbilical fissure (or its proximity), providing venous drainage for hepatic segments 3 and 4. Its preservation carries a potential importance in extended right hemi‐hepatectomy, left lateral segmentectomy and extended segment 2 resections. Methods: Consecutive 1‐mm slice thickness portovenous phase intravenous contrast computed tomography (CT) scans of the abdomen performed were retrospectively reviewed during the period of June 2019 to July 2019, with two independent investigators investigating the presence of UFV, its course, insertion and relation to the umbilical fissure. Results: A total of 244 CTs were identified and 186 included. The UFV was identified on 72.8% of participants, 109 (81.4%) drained into the main left hepatic vein, while the remaining ones drained either from the main middle hepatic vein (16.4%) or the bifurcation between main left and middle hepatic vein (2.2%). The veins course lay 2 mm or less along the length of umbilical fissure in 39.5%, while 57.5% ran within 1 cm along the length of the umbilical fissure. Conclusion: Pre‐operative identification of UFV could assist in operative planning. The vein can be used as a landmark in surgery and should be preserved in left lateral segmentectomy and extended right hepatectomy to avoid parenchymal congestion of remnant segments. Abstract : The umbilical fissure vein (UFV) is a tributary of either the left or middle hepatic vein and it usually drains hepatic segment 3 and 4. This paper investigates computed tomography scan identification of the UFV and potential benefits in use in pre‐operative planning.